Redox mediators modify end product distribution in biomass fermentations by mixed ruminal microbes in vitro - Nerdahl, Michael A; Weimer, Paul J (AMB Express, 2015)
The fermentation system of mixed ruminal bacteria is capable of generating large amounts of short-chain volatile fatty acids (VFA) via the carboxylate platform in vitro. These VFAs are subject to elongation to larger, more energy-dense products through reverse β-oxidation, and the resulting products are useful as precursors for liquid fuels production. This study examined the effect of several redox mediators (neutral red, methyl viologen, safranin O, tannic acid) as alternative electron carriers for mixed ruminal bacteria during the fermentation of biomass (ground switchgrass not subjected to other pretreatments) and their potential to enhance elongation of end-products to medium-chain VFAs with no additional run-time. Neutral red (1 mM) in particular facilitated chain elongation, increasing average VFA chain length from 2.42 to 2.97 carbon atoms per molecule, while simultaneously inhibiting methane accumulation by over half yet maintaining total C in end products. The ability of redox dyes to act as alternative electron carriers suggests that ruminal fermentation is inherently manipulable toward retaining a higher fraction of substrate energy in the form of VFA.